2014
DOI: 10.5194/acpd-14-9729-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How sensitive is the recovery of stratospheric ozone to changes in concentrations of very short lived bromocarbons?

Abstract: Abstract. Naturally produced very short-lived substances (VSLS), like bromocarbons, account for almost a quarter of the current stratospheric inorganic bromine, Bry. Following VSLS oxidation, bromine radicals (Br and BrO) can catalytically destroy ozone. The extent to which possible increases in surface emissions or transport of these VSLS bromocarbons to the stratosphere could counteract the effect of halogen reductions under the Montreal Protocol is an important policy question. Here by using a chemistry–cli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
9
18
1
Order By: Relevance
“…If we assume that this emission ratio of 5 is appropriate for the SE Asian region, (10 • N to 20 • S, 90 • E to 160 • E, as used by Pyle et al, 2011), and recalling that the air mass histories in the two periods of these two studies are quite similar, then we could derive an emission estimate for CHBr 3 from the regional CH 2 Br 2 emission. That value is not observationally constrained; instead we use the SEA regional CH 2 Br 2 emission from an updated version of the Warwick et al (2006) inventory (as used by Yang et al, 2014). As before, spatially uniform ocean emissions of CH 2 Br 2 are assumed in the tropics, but emissions are halved, so that the global total of 57 Gg CH 2 Br 2 /yr is more consistent with the recent studies of Liang et al (2010) and Ordonez et al (2012).…”
Section: Emission Ratiossupporting
confidence: 58%
“…If we assume that this emission ratio of 5 is appropriate for the SE Asian region, (10 • N to 20 • S, 90 • E to 160 • E, as used by Pyle et al, 2011), and recalling that the air mass histories in the two periods of these two studies are quite similar, then we could derive an emission estimate for CHBr 3 from the regional CH 2 Br 2 emission. That value is not observationally constrained; instead we use the SEA regional CH 2 Br 2 emission from an updated version of the Warwick et al (2006) inventory (as used by Yang et al, 2014). As before, spatially uniform ocean emissions of CH 2 Br 2 are assumed in the tropics, but emissions are halved, so that the global total of 57 Gg CH 2 Br 2 /yr is more consistent with the recent studies of Liang et al (2010) and Ordonez et al (2012).…”
Section: Emission Ratiossupporting
confidence: 58%
“…In addition to the instruments at Eureka (PEARL‐GBS, ozonesondes, radiosondes, and MMCR), several other data sets were employed in this study: the Global Ozone Monitoring Experiment‐2 (GOME‐2) satellite tropospheric BrO columns [ Begoin et al , ; Blechschmidt et al , ], the Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT) model [ Draxler and Hess , ; Draxler et al , ], the European Centre for Medium‐Range Weather Forecasts (ECMWF) interim meteorological data (ERA‐interim data) (wind speed, boundary layer height, and large‐scale snow‐fall) [ Dee et al , ], the National Snow and Ice Data Center (NSIDC) data (sea ice age and snow depth over sea ice) [ Kurtz et al , ], and the UM‐UKCA chemistry‐climate model [ Morgenstern et al , ; Yang et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…The total amount of inorganic Br y (from both halocarbons and sea salt) in the stratosphere is about 20 pptv [ Braesicke et al , ]. A number of heterogeneous reactions on atmospheric particles (including sulphate aerosols and polar stratospheric clouds) have been included in the model to account for interhalogen (chlorine and bromine) reactivation as in the recent study by Braesicke et al [] and Yang et al []. In the polar boundary layer, heterogeneous reactivation of inactive bromine on sulphate aerosols has been considered with sulphate field being monthly climatology data from the CLASSIC aerosol scheme [ Johnson et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…Frieler et al [2006] showed inclusion of bromine from VSLS led to better agreement between observed and modeled loss of Arctic ozone for a particular winter. Yang et al [2014] made a rough estimate of 6-8 years later recovery of the Antarctic ozone hole due to 5 ppt of bromine from VSLS based on time-slice experiments with various chlorine and bromine levels. Yang et al [2014] made a rough estimate of 6-8 years later recovery of the Antarctic ozone hole due to 5 ppt of bromine from VSLS based on time-slice experiments with various chlorine and bromine levels.…”
Section: Introductionmentioning
confidence: 99%